OTUB1 triggers lung cancer development by inhibiting RAS monoubiquitination. Issue 3 (8th February 2016) - Baietti, Maria Francesca; Simicek, Michal; Abbasi Asbagh, Layka; Radaelli, Enrico; Lievens, Sam; Crowther, Jonathan; Steklov, Mikhail; Aushev, Vasily N; Martínez García, David; Tavernier, Jan; Sablina, Anna A
Abstract: Activation of the RAS oncogenic pathway, frequently ensuing from mutations in RAS genes, is a common event in human cancer. Recent reports demonstrate that reversible ubiquitination of RAS GTPases dramatically affects their activity, suggesting that enzymes involved in regulating RAS ubiquitination may contribute to malignant transformation. Here, we identified the de‐ubiquitinase OTUB1 as a negative regulator of RAS mono‐ and di‐ubiquitination. OTUB1 inhibits RAS ubiquitination independently of its catalytic activity resulting in sequestration of RAS on the plasma membrane. OTUB1 promotes RAS activation and tumorigenesis in wild‐type RAS cells. An increase of OTUB1 expression is commonly observed in non‐small‐cell lung carcinomas harboring wild‐type KRAS and is associated with increased levels of ERK1/2 phosphorylation, high Ki67 score, and poorer patient survival. Our results strongly indicate that dysregulation of RAS ubiquitination represents an alternative mechanism of RAS activation during lung cancer development. Synopsis: The regulation of RAS mono‐ubiquitination by OTUB1 is an alternative mechanism of RAS activation during lung cancer development. OTUB1 negatively regulates RAS mono‐ubiquitination resulting in sequestration of RAS on the plasma membrane. OTUB1 promotes RAS signaling and tumorigenic growth of wild‐type KRAS lung adenocarcinoma cells. OTUB1 up‐regulation is associated with poorer survival of wild‐type KRAS lung adenocarcinoma patients. Abstract : The regulation of RAS mono‐ubiquitination by OTUB1 is an alternative mechanism of RAS activation during lung cancer development.